2020
DOI: 10.36547/nbc.v19i1.581
|View full text |Cite
|
Sign up to set email alerts
|

Perspective pretreatment method of beech and poplar wood and wheat straw in 2G biofuel production processing

Abstract: Monosaccharides such as glucose, xylose and arabinose are the main monomer units of which cellulose and hemicelluloses are composed. The cellulose and hemicelluloses content in many biomass species makes them suitable for 2G bioethanol production. Today, when 1G bioethanol production is closely monitored due to its enormous consumption of food raw materials such as wheat or corn grains, larger companies are gradually moving to pilot operations of 2G bioethanol production. However, cellulose and hemicelluloses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…HPLC analysis showed that the monosaccharides in obtained hydrolysates had a different elution time (Table 1). The elution time did not depend on concentration of hydrolyzed monosaccharides however, it depended on set-up and conditions of HPLC method (Pažitný et al 2020b). inhibition products ranged from 4.4 g.L -1 to 4.9 g.L -1 among all the hydrolysates obtained from pretreated beech particles.…”
Section: Hplc Chromatograms Of Stexp and C-stexp Samples Of Dendromassmentioning
confidence: 93%
See 3 more Smart Citations
“…HPLC analysis showed that the monosaccharides in obtained hydrolysates had a different elution time (Table 1). The elution time did not depend on concentration of hydrolyzed monosaccharides however, it depended on set-up and conditions of HPLC method (Pažitný et al 2020b). inhibition products ranged from 4.4 g.L -1 to 4.9 g.L -1 among all the hydrolysates obtained from pretreated beech particles.…”
Section: Hplc Chromatograms Of Stexp and C-stexp Samples Of Dendromassmentioning
confidence: 93%
“…Today it often replaces fossil fuels used in heating plants producing heat and hot water for households (Plešingerová et al 2020;Nosek et al 2021). In recent years, however, attention has focused not only on the production of biopellets and other fuel products based on dendromass, but also on research into the disintegration of dendromass through its pretreatment and hydrolysis, especially enzymatic hydrolysis (Wang et al 2013;Pažitný et al 2020a and2020b). Dendromass-based hydrolysates can then be used in the alcoholic fermentation process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations